2017
DOI: 10.3892/ol.2017.6571
|View full text |Cite
|
Sign up to set email alerts
|

Expression and clinical significance of SATB1 and TLR4 in breast cancer

Abstract: This study investigated the expression of special AT-rich sequence-binding protein 1 (SATB1) and toll-like receptor 4 (TLR4) protein in breast cancer and its clinical significance. We collected breast cancer tissues from 120 patients and adjacent non-cancerous tissue from 53 patients. SATB1 was expressed in 89 cases of breast cancer (74.17%) and in 7 cases of adjacent non-cancerous tissue (13.21%). TLR4 was expressed in 70 cases of breast cancer tissues (58.33%) and in 48 cases of adjacent non-cancerous tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 33 publications
(32 reference statements)
0
13
0
Order By: Relevance
“…An increased SATB1 protein level in breast cancer cases as compared to normal breast tissues, and its positive correlation with a higher histological grade and a positive HER-2 status were also further reported by Liu et al [52]. Similarly, Wang and co-workers observed that SATB1′s expression positively correlated with the size and grade of the tumour, the presence of lymph node metastasis, the stage of the disease and the tumour ER status [53]. A positive relationship between the level of SATB1 and a poor degree of tumour differentiation was also demonstrated by Kobierzycki et al, but their results did not reach statistical significance [54].…”
Section: Satb1’s Role In Cancer Progressionmentioning
confidence: 54%
“…An increased SATB1 protein level in breast cancer cases as compared to normal breast tissues, and its positive correlation with a higher histological grade and a positive HER-2 status were also further reported by Liu et al [52]. Similarly, Wang and co-workers observed that SATB1′s expression positively correlated with the size and grade of the tumour, the presence of lymph node metastasis, the stage of the disease and the tumour ER status [53]. A positive relationship between the level of SATB1 and a poor degree of tumour differentiation was also demonstrated by Kobierzycki et al, but their results did not reach statistical significance [54].…”
Section: Satb1’s Role In Cancer Progressionmentioning
confidence: 54%
“…The multivariate analysis indicated that TLR4 is independent prognostic factors with high expression associated to a shorter DFS and OS in BC. This is not surprising considering that TLR4 is related to cancer aggressiveness and poor clinical outcome (20,42,43,(50)(51)(52). NLRP3 expression showed a slight, albeit not significant, association with DFS and this association to the clinical effects of BC is a new compelling point.…”
Section: Discussionmentioning
confidence: 97%
“…Since the discovery of SATB1, its role in the pathogenesis of various cancers has been investigated. Importantly, upregulation of SATB1 has been shown to promote many pathological features across a wide range of cancers [38,39] including breast [1,[40][41][42], colorectal [2,[43][44][45], lung [46,47], nasopharyngeal [48], oesophageal [3,49,50], gastric [51,52], pancreatic [53,54], ovarian [32,55,56], liver [57][58][59], prostate [60][61][62][63], bladder [64,65], and brain [66][67][68][69][70]. In most cancers, the SATB1 expression is positively associated with increased tumour size, lymph node involvement and metastasis [71,72], tumour progression [1,2], poor prognosis [50,56] and reduced overall survival [49,54].…”
Section: Satb1 and Cancermentioning
confidence: 99%